Impact of chemotherapy on the outcome of osteosarcoma of the head and neck in adults. Issue 1 (10th August 2016) - Boon, Eline; van der Graaf, Winette T. A.; Gelderblom, Hans; Tesselaar, Margot E. T.; van Es, Robert J. J.; Oosting, Sjoukje F.; de Bree, Remco; van Meerten, Esther; Hoeben, Ann; Smeele, Ludi E.; Willems, Stefan M.; Witjes, Max J. H.; et al.
Abstract: Background: There is an ongoing debate about the value of (neo‐)adjuvant chemotherapy in high‐ and intermediate‐grade osteosarcoma of the head and neck. Methods: All records of patients older than 16 years diagnosed with osteosarcoma of the head and neck in the Netherlands between 1993 and 2013 were reviewed. Results: We identified a total of 77 patients with an osteosarcoma of the head and neck; the 5‐year overall survival (OS) was 55%. In 50 patients with surgically resected high‐ or intermediate‐grade osteosarcoma of the head and neck younger than 75 years, univariate and multivariable analysis, adjusting for age and resection margins, showed that patients who had not received chemotherapy had a significantly higher risk of local recurrence (hazard ratio [HR] = 3.78 and 3.66, respectively). Conclusion: In patients younger than 75 years of age with surgically resected high‐ and intermediate‐grade osteosarcoma of the head and neck, treatment with (neo‐)adjuvant chemotherapy resulted in a significantly smaller risk of local recurrence. Therefore, we suggest (neo‐)adjuvant chemotherapy in patients amenable to chemotherapy. © 2016 The Authors Head & Neck Published by Wiley Periodicals, Inc. Head Neck 39: 140–146, 2017